Intervention effects of low-molecular-weight chondroitin sulfate from the nasal cartilage of yellow cattle on lipopolysaccharide-induced behavioral disorders: regulation of the microbiome-gut-brain axis - Deng, Yuxuan; Li, Qingyuan; Song, Junxian; Guo, Rui; Ma, Tianchen; Liu, Zhigang; Liu, Qian (Frontiers in Nutrition, 2024)
Chondroitin sulfate (CS) is a sulfated linear polysaccharide with different functional activities, including antioxidant, anti-inflammatory, lipid-lowering, and immune regulation. As natural sulfated polysaccharides have high molecular weight, high apparent viscosity, low water solubility, complex structure, and high negative charge, they have difficulty binding to receptors within cells across tissue barriers, resulting in low bioavailability and unclear structure-activity relationships. In this study, an H2O2-Vc oxidative degradation system was employed to perform environmentally friendly and controllable degradation of CS extracted from the nasal cartilage of Shaanxi Yellow cattle. Two low-molecular-weight chondroitin sulfates (LMWCSs), CS-1 (14.8 kDa) and CS-2 (50.9 kDa), that exhibit strong in vitro free radical scavenging ability were obtained, and their structures were characterized. Mice intraperitoneally administered lipopolysaccharide (LPS) were used to explore the cognitive intervention effects of LMWCS. Supplementing CS-1 and CS-2 significantly downregulated the levels of the serum inflammatory factors, TNF-α and IL-1β, promoted the expression of GSH in the brain, and inhibited the production of the lipid peroxidation product, malondialdehyde (MDA), ultimately inhibiting LPS-induced cognitive impairment in mice. Surprisingly, compared to the LPS model group, the abundances of Streptococcus, Eisenbergiella, Vampirovibrio, Coprococcus, Enterococcus and Lachnoanaerobaculum were significantly increased in the intestines of mice in the CS-1 and CS-2 group, whereas those of Parabacteroides and Mycoplasma were significantly decreased. Altogether, this study provides a theoretical basis for the comprehensive utilization of agricultural and animal resources and the application of brain nutrition, anti-inflammatory, and LMWCS health products.